Politicking in global elite sports - Koshkin, A. P.; Novikov, A. V.; Cherdantsev, V. V.; Rozhina, E. Yu. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze the ongoing political campaign of 2015-2018 with its doping scandal geared to demonize the Russian professional sports system. Historical analysis, comparative analysis and institutional study methods were applied for the study purposes as a conceptual basis. The study analyses the global sports in the context of recent policies pursued in the new millennium with a special attention to the Russian professional sport demonizing politicking campaign and its geopolitical drivers of special degrading influence on the top-ranking international sport events including the Olympic Games and 2018 FIFA World Cup. The key question now is whether or not the global sport system will be able to clean itself of the biased politicking and dirty campaigning.